"If they don't listen to us, they deserve it": The effect of external efficacy and anger on the perceived legitimacy of hacking. (September 2020) - Heering, Maria S.; Travaglino, Giovanni A.; Abrams, Dominic; Goldsack, Emily
We conducted two studies examining the factors underlying individuals' legitimization of hackers (digital actors operating on the internet). Drawing on the social banditry framework, and research on political action, we focused on the mediating role of anger in the association between external political efficacy and perceived legitimization of hackers' actions. Specifically, we manipulated whether the system was responsive to participants' demands following unfair treatment in a university (Study 1) and in an online work platform (Study 2) context. In Study 1 ( N = 259) British undergraduate students read about unfair "grading" practices. They were then informed that the management was either willing (high external political efficacy) or unwilling (low external political efficacy) to investigate the matter. In Study 2 ( N = 222), British participants were recruited via Prolific Academic and were presented with a scenario describing an unfair rejection of their work. They were then informed that the platform admin was either willing or not willing to investigate their case. Across studies, participants were informed that hackers had attacked the website. Supporting the social banditry framework, results indicated that individuals who perceive the system as unresponsive to their demands tended to legitimize hackers' actions via stronger perceived anger against the system. Implications of the results, and future directions are discussed.